2020
DOI: 10.1021/acs.iecr.0c00315
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Crystalline Composite Membranes Composed of Smectic Imidazolium Hydrogen Sulfate and Polyvinyl Alcohol for Anhydrous Proton Conduction

Abstract: Proton exchange membranes are widely used in fuel cells for directly converting chemical energy into electrical energy. Commercially successful perfluorosulfonic acid membranes do not have the ability of proton conduction under dry conditions. Owing to the advantages of simplified thermal and water management, anhydrous proton conductive materials are appealing. Herein, a novel liquid crystalline composite membrane is prepared by a solution cast method for anhydrous proton conduction at elevated temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Ref. : PVA/MPPIS; 81 PVA/nZnO; 75 PVA/DBEG‐G‐SiO 2 ; 82 PVA/SSA/GO; 83 PVA/Sulfonated nSiO 2 /GA; 70 PVA/SiWA/nSiO 2 /SSA; 73 SPEEK/PVA@GO‐NF; 66 PVA/PAMPS‐ g ‐FSN/GA; 84 Propane sultone/PVA/SSA/GO; 23 PVA/PAN‐ co ‐PSSA/PAMPS‐Si; 68 PVA/TEOS/SSA; 85 PVA/nSiO 2 /SSA; 86 PVA/SCNT/SSA; 69 PVA/SGO; 74 H 3 PO 4 ‐imbibed PAM/PVA; 87 HPA/PVA‐ g ‐Aam (GA crosslinked); 88 PVA/PSSA‐SiO 2 /SSA/GA; 71 PVA/SSA; 77 SPEEK/PVA/TEOS; 67 PPVA/PHB/SiO 2 ‐P NPs; 80 PVA/SPANi‐GO; 89 PVA/PAMPS/ZIF; 78 and PVDF/PPVA/nTiO 2 76 . Abbreviations: Aam, acrylamide; DBEG, 1,4‐diglycidyl butane ether; FSN, fumed silica nanoparticles; GA, glutaraldehyde; GO, graphene oxide; HPA, heteropolyacid (H 3 PW 12 O 40 ); MPPIS, liquid crystal: 1‐methyl‐3‐[6‐[4‐(trans‐4‐pentylcyclohexyl)‐ phenoxy]hexyl]imidazolium hydrogen sulfate; PAM, polyacrylamide; PFSA, perfluorosulfonic acid; PPVA, phosphonated PVA; PVDF, poly(vinylidene difluoride); SCNT, sulfonated carbon nanotubes; SiO 2 ‐P NPs: phosphonated silica nanoparticles; SiWA, silicotungstic acid; SPEEK, sulfonate poly(ether ketone); SSA, sulfosuccinic acid; TEOS, tetraethyl orthosilicate; ZIF, zeolite‐imidazole framework…”
Section: Pva‐based Membranes For Fuel Cellsmentioning
confidence: 99%
“…Ref. : PVA/MPPIS; 81 PVA/nZnO; 75 PVA/DBEG‐G‐SiO 2 ; 82 PVA/SSA/GO; 83 PVA/Sulfonated nSiO 2 /GA; 70 PVA/SiWA/nSiO 2 /SSA; 73 SPEEK/PVA@GO‐NF; 66 PVA/PAMPS‐ g ‐FSN/GA; 84 Propane sultone/PVA/SSA/GO; 23 PVA/PAN‐ co ‐PSSA/PAMPS‐Si; 68 PVA/TEOS/SSA; 85 PVA/nSiO 2 /SSA; 86 PVA/SCNT/SSA; 69 PVA/SGO; 74 H 3 PO 4 ‐imbibed PAM/PVA; 87 HPA/PVA‐ g ‐Aam (GA crosslinked); 88 PVA/PSSA‐SiO 2 /SSA/GA; 71 PVA/SSA; 77 SPEEK/PVA/TEOS; 67 PPVA/PHB/SiO 2 ‐P NPs; 80 PVA/SPANi‐GO; 89 PVA/PAMPS/ZIF; 78 and PVDF/PPVA/nTiO 2 76 . Abbreviations: Aam, acrylamide; DBEG, 1,4‐diglycidyl butane ether; FSN, fumed silica nanoparticles; GA, glutaraldehyde; GO, graphene oxide; HPA, heteropolyacid (H 3 PW 12 O 40 ); MPPIS, liquid crystal: 1‐methyl‐3‐[6‐[4‐(trans‐4‐pentylcyclohexyl)‐ phenoxy]hexyl]imidazolium hydrogen sulfate; PAM, polyacrylamide; PFSA, perfluorosulfonic acid; PPVA, phosphonated PVA; PVDF, poly(vinylidene difluoride); SCNT, sulfonated carbon nanotubes; SiO 2 ‐P NPs: phosphonated silica nanoparticles; SiWA, silicotungstic acid; SPEEK, sulfonate poly(ether ketone); SSA, sulfosuccinic acid; TEOS, tetraethyl orthosilicate; ZIF, zeolite‐imidazole framework…”
Section: Pva‐based Membranes For Fuel Cellsmentioning
confidence: 99%
“…5−7 However, the high ion-exchange capacity usually leads to excessive swelling under the hydrated condition and thus affects structural stability and further performance optimization. 8,9 In recent years, porous organic polymers (POPs), such as porous aromatic frameworks (PAFs), polymers of intrinsic microporosity (PIMs), and covalent organic frameworks (COFs), have attracted global attention due to their rigid scaffold structure and tunable pore size. 10−13 The intrinsic nanopores of polymer scaffold not only provide a platform for constructing transport pathways but also exhibit high structural stability even under high ion-exchange capacity 14,15 Current strategies for developing POP-based proton conductors rely on doping with external proton carriers or postmodifications with chlorosulfonic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, sufficient proton donor groups and acceptors are highly required to obtain high proton conductivity. Conventional polyelectrolytes are based on flexible functional polymers, such as Nafion, sulfonated poly­(ether ether ketone) (SPEEK), sulfonated polysulfone (SPS), etc. However, the high ion-exchange capacity usually leads to excessive swelling under the hydrated condition and thus affects structural stability and further performance optimization. , …”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid crystals, combining the synergistic features of nonvolatile ionic liquids and dynamically ordered liquid crystals, are promising candidates as efficient and stable electrolytes for providing multiscale channels capable of ion transport. Previously, we showed that liquid crystal nanostructures could promote Grotthuss-type charge transport in thiolate/disulfide (T – /T 2 )-based smectic electrolytes for DSSCs . The organic T – /T 2 redox, possessing properties of noncorrosion, transparency, and noninhibition to radical polymerization, is promising to rival the traditional iodide/triiodide redox for all-solid-state DSSC preparation .…”
Section: Introductionmentioning
confidence: 99%